Examining the Correlation Between Speed and Change of Direction Running Speed (CODS) in Football - Horváth, Tamás; Müller, Anetta; Karap, Bálint; Bíró, Melinda (Stadium - Hungarian Journal of Sport Sciences, 2025)
The correlation between speed and change-of-direction running speed (CODS) remains unclear, as indicated by the results of previous research. One reason may be that researchers have used different tests to investigate the speed of running with a change of direction (CODS), where the number of direction changes, the angle, the total length of the running test, and the time required to complete the test vary. The researchers agree that agility is not the same as straight-line running speed, but suggest that further studies are needed to determine the relationship. Regarding the relationship between speed and agility, the results showed a consistent trend that faster players tend to perform better on the agility test. Still, we could only statistically confirm this at 20 and 30 metres. Only for the agility test in the right direction was there a significant correlation between 20 and 30 meters alone. Our results indicate that both agility and and CODS require different developmental stages.